(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: The impact of assisted reproductive technology (ART) on Swiss demography was quantified. From 1993 to 2012 the number of deliveries, including multiples, generated by ART was compared with overall delivery numbers. Swiss experts in ART collaborated in a consensus to increase successful outcomes, to reduce the incidence of complications of ART and to validate recommendations through statistical review of available data. METHODS: Data generated between 1993 and 2012 and published by the Federal Office of Statistics (BfS) were compared with the Swiss database on ART (FIVNAT-CH) as organised by the Swiss Society of Reproductive Medicine (SGRM). From these analyses a panel of Swiss experts in ART extracted recommendations to improve current practice, to prevent complications related to ART and to recommend changes in current Swiss legislation dealing with ART. RESULTS: Since 1993 the age of women giving birth rose together with the number of women asking for ART. This demographic trend was reflected in a rise in the number of deliveries generated by ART (in 2012: 2.2%) and the proportion of multiple births (in 2012: 17.6%). The outcome of ART was most negatively influenced by the age of the treated patient. The number of retrieved oocytes decisively impacted the likelihood of delivery, the risk of multiple births and the incidence of ovarian hyperstimulation syndrome. CONCLUSIONS: Optimal ovarian stimulation should be designed for the retrieval of 10 to 15 oocytes per treatment. Swiss legislation should enable and stimulate a policy of elective single embryo transfer to avoid multiple births.